Active composite brazing filler metal suitable for welding ceramic and copper material and preparation method of active composite brazing filler metal

By constructing an active composite solder with an active coating on the surface of the metal foil, the problems of thermal expansion coefficient difference and welding reliability in the welding of ceramics and copper materials are solved, and low-cost, large-size ceramics and copper materials can be welded efficiently, which is suitable for the connection of a variety of heterogeneous materials.

CN120717802APending Publication Date: 2025-09-30HANGZHOU HUAGUANG ADVANCED WELDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510885781.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-30
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

In the existing technology, there are large differences in thermal expansion coefficient and melting point between ceramic and metal welding. The traditional active solder preparation process is complex and costly, the electroplating process is highly polluting, making it difficult to achieve mass production of large sizes or complex structures, and the welding reliability is poor.

Method used

An active composite solder consisting of a plastic matrix layer and an active coating is used. By constructing a coating containing active elements such as Ti and Zr on the surface of the metal foil, a gradient diffusion layer is formed at low temperature using a coating process to achieve efficient connection between ceramics and copper materials. The coating material can regulate the distribution and diffusion path of the active elements.

Benefits of technology

It achieves low-cost, high-reliability welding of large-size ceramics and copper materials, solves the problems of numerous processes and pollution in traditional processes, improves the contact area and reliability of the welding interface, and is suitable for the connection of various ceramics and metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120717802A_ABST
    Figure CN120717802A_ABST
Patent Text Reader

Abstract

The invention relates to active composite brazing filler metal suitable for welding ceramics and copper materials and a preparation method of the active composite brazing filler metal. The active composite brazing filler metal is composed of a plastic matrix layer and an active coating. The plastic matrix layer is a metal foil containing at least one of Ag, Cu and Ni; the active coating is an active metal layer arranged on the plastic matrix layer, and active metal is selected from at least one of Ti, Zr, Cr, Hf, V and Nb. The active coating is divided into two layers, the upper layer is a TiH2 active metal layer, and the lower layer is a TiH2 active metal layer. The metal foil is an AgCu28 foil, and the active coating is a TiH2 active brazing filler metal. The preparation method of the active composite brazing filler metal comprises the steps that S1, the metal foil and the active composite brazing filler metal paste are prepared; s2, the metal foil is coated with the active composite brazing filler metal paste; and S3, baking is conducted in the environment of 80-150 DEG C, and the active composite brazing filler metal is formed. The method is simple, reasonable, high in efficiency, low in cost and high in reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an active composite solder suitable for welding ceramics and copper materials and a preparation method thereof, and is mainly suitable for welding between ceramics and copper materials. Background Art

[0002] Due to ceramics' excellent high-temperature resistance, high mechanical strength, and excellent chemical stability, heterojunction joining of ceramics and metals holds broad application prospects in aerospace, automotive, and other fields. Currently, the main methods for heterojunction joining ceramics and metals include brazing, diffusion welding, and transient liquid phase joining, with brazing being the most commonly used. However, due to the significant differences in thermal expansion coefficients and melting points between ceramics and metals, metallization of the ceramic surface is often required before joining.

[0003] Active brazing filler metals are the most commonly used brazing filler metals for ceramic joining. However, the traditional hot-pressing and sintering method for producing active brazing filler metals is technically demanding, requiring a series of steps, including powder preparation, sintering, and rolling. This makes it unsuitable for producing large-scale or complex-sized filler metals. Furthermore, the high manufacturing cost of existing active brazing fillers limits their mass production and widespread application.

[0004] Existing technologies have attempted to deposit an active metal layer on the solder surface through electroplating, but there are obvious shortcomings: the wastewater, waste gas and waste residue generated during the electroplating process contain heavy metal ions, organic pollutants, etc., which affect the ecological balance; electroplating has many restrictions on the substrate, usually requiring a clean surface, and the electroplated layer is usually a single substance. Compounds are usually difficult to plate onto the substrate surface, limiting the range of choices for plating materials; and the electroplating process relies on the direct reaction of metal elements, which is limited by the singleness of the composition and the rapid diffusion characteristics. It is easy to cause local aggregation of active elements during brazing, easily forming a brittle phase layer, and affecting reliability. Summary of the Invention

[0005] The technical problem solved by the present application is to overcome the above-mentioned deficiencies in the prior art and to provide an active composite solder suitable for welding ceramics and copper materials and a preparation method thereof.

[0006] The technical solution adopted by this application to solve the above-mentioned technical problems includes: an active composite brazing filler metal suitable for welding ceramics and copper materials, characterized by: comprising a plastic base layer and an active coating; the plastic base layer is a metal foil containing at least one element of Ag, Cu, and Ni; the active coating is an active metal layer disposed on the plastic base layer, and the active metal is selected from at least one of Ti, Zr, Cr, Hf, V, and Nb. This application creatively constructs a surface active coating containing active elements such as Ti, Zr, and Cr on the surface of the metal foil, and facilitates the free implementation of local, single-sided, or double-sided composites according to specific application requirements. The active elements in the surface active coating release active atoms during heating, chemically reacting with the ceramic surface to form a gradient diffusion layer. At the same time, some active elements react with Cu to form nano-scale Cu-Ti, Cu-Zr, and other intermetallic compounds, thereby strengthening the weld. By adjusting the type of active elements and the coating thickness, it can adapt to the connection requirements of various ceramics such as aluminum oxide, silicon nitride, and zirconium oxide with metals such as copper and copper alloys.

[0007] The active coating layer consists of two layers, with an upper ZrH2 active metal layer and a lower TiH2 active metal layer.

[0008] The thickness of the metal foil is 0.01-0.3 mm, and the maximum length and width are between 20-200 mm. The preferred range of the maximum length and width of the metal foil is between 60-150 mm.

[0009] The active coating is formed by mixing active metal powder with a particle size of 0.5-80 μm and an organic carrier.

[0010] The mass ratio of the plastic matrix layer to the active coating is between 99.5:0.5 and 70:30, and the thickness of the active coating is between 10-200 μm.

[0011] The metal foil is AgCu 28 The active coating is TiH2 active solder.

[0012] The technical solution adopted by the present application to solve the above technical problems also includes: a method for preparing the above active composite brazing material suitable for welding ceramics and copper materials, which is characterized by comprising the following steps: S1 prepares metal foil and active composite solder paste; The S2 active composite solder paste is placed on the metal foil by a coating process (printing, spraying, dipping or brushing); S3 The metal foil coated with active composite solder paste is baked at 80~150℃ to form active composite solder.

[0013] As a special case, the active composite solder paste is formed by mixing the above-mentioned active metal powder with an organic carrier. The organic carrier has a certain adhesion effect and can fix the active metal powder on the plastic matrix layer.

[0014] The organic carrier is selected from at least one of acrylic resin polymers, higher hydrocarbon resins, PVP, polyethylene glycol, polyvinyl alcohol, polyvinyl butyral, polyethylene, polypropylene, polyvinyl chloride, polyurethane, epoxy resin, methyl cellulose, carboxymethyl cellulose, ethyl cellulose, hydroxyethyl cellulose, propyl cellulose, hydroxypropyl cellulose, and hydroxypropyl methyl cellulose.

[0015] The active composite solder paste is provided on the metal foil through a coating process, which may include: S21 Place the metal foil under the screen and fit it tightly; The S22 active composite solder paste is spread on one side of the screen, and the active composite solder paste is printed on the other side using a scraper.

[0016] The printing speed in step S22 is 20 mm / s, and the scraper angle (the angle between the scraper center line and the screen plane) is 65°, so that the active composite solder paste can be printed on the surface of the metal foil.

[0017] The active composite solder paste is provided on the metal foil through a coating process or it can be: S23: a certain active composite solder paste (particularly TiH2 active metal paste) is screen-printed on the metal foil; S24 screen prints another active composite solder paste (a special case of ZrH2 active metal paste) onto the metal foil.

[0018] The base metal foil of this application has good plasticity and can be produced into large-sized strips through traditional melting and rolling processes, with a simple preparation method. Subsequently, a layer of active composite solder coating is applied to the surface of the base metal foil. The content of the active composite solder coating is controlled by coating force and mold parameters. After heating to an appropriate temperature, the active composite solder coating and the metal foil are bonded together to form a single unit, making it more suitable for the preparation of large-sized welding materials.

[0019] Advantages and positive effects of this application: 1. The traditional hot pressing and sintering powder preparation, sintering, and rolling process are complicated. The preparation process of the active composite solder of the present application is simple. Compared with the traditional active solder, the preparation cost is low, which is conducive to promotion and use. 2. Compared with the electroplating process and the traditional hot pressing sintering process, the active composite solder prepared by coating a layer of active coating on the surface of the metal foil has a simple preparation method, low production technology requirements, and can be mass-produced in large sizes; 3. Compared with traditional hot-pressed active solder, this application combines the characteristics of low-temperature curing (80-150°C) and high-temperature directional energy release (800-950°C). The active composite solder made through the coating process does not cause the increase of active elements and thus reduce the material's processability, thus solving the problem of the material becoming hard and brittle and difficult to roll when the active element content increases; 4. The coating process can precisely control the spatial distribution of active elements. Through multi-layer coating or patterned printing, localized active element enrichment can be achieved, solving the problem of uneven element diffusion in large-scale joints. This application can construct a gradient active layer through multi-layer coating, using the timing control mechanism of Ti preferentially diffusing to form a reaction layer and Zr subsequently diffusing to strengthen the weld, breaking through the structural characteristics of traditional hot pressing and electroplating. 5. Compared with the electroplating process, the coating process can precisely control the decomposition kinetics and diffusion path of the active elements. The electroplating process relies on the direct reaction of the metal element, which is limited by the single composition and rapid diffusion characteristics, and is prone to forming a brittle phase layer. The coating process, on the other hand, controls the thermal decomposition and diffusion path of the active compound. The hydride, as the coating material, releases trace amounts of hydrogen during brazing to further remove oxides, achieving an in-situ reduction and purification effect, and improving wettability. The active elements in the coating process diffuse synergistically through the grain boundaries and bulk diffusion of the metal matrix, suppressing explosive diffusion, achieving a synergistic enhancement of the thickness of the ceramic interface reaction layer and the weld strengthening phase (Cu-Ti / Zr intermetallic compound), and overcoming the problem of interfacial cracking caused by thermal expansion mismatch of heterogeneous materials. On the other hand, the active coating type of this coating process is not limited, and the active coating particles can reach the micron level. The micron coating particles can better melt, decompose and diffuse without aggregation, increasing the contact area of ​​the brazing interface. The micro-battery reaction formed locally during the brazing process enhances the mutual diffusion of metal ions, which is beneficial to improving the reliability of the brazing interface. Electroplating is prone to insufficient diffusion of active elements and aggregation. 6. Expand the applicable material system. By matching different active elements with the matrix alloy composition, high-reliability connections can be achieved between ceramics such as Al2O3 / SiC and metals such as Cu. 7. Freely select local, single-sided, or double-sided lamination based on the application scenario to achieve precise control of active solder materials and regulate the spatial distribution of active elements. By precisely matching screen parameters and process conditions, the coating process can achieve a dynamic balance of directional release, diffusion, and reaction of active elements. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the active composite solder printing process of this application.

[0021] Figure 2 This is a structural diagram of the active composite solder of the present application.

[0022] Figure 3 This is another structural schematic diagram of the active composite solder of the present application. DETAILED DESCRIPTION

[0023] The present application will be further described in detail below with reference to the accompanying drawings and examples. The following examples are intended to explain the present application but the present application is not limited to the following examples.

[0024] See also Figures 1 to 3 In Example 1 of the present application, TiH2 powder is used as raw material to prepare active composite solder paste 3, which is printed on a metal foil 1 (AgCu in this example) by screen printing 2. 28 An active composite solder paste coating is prepared on the surface of the AgCu foil. The metal foil coated with the active composite solder paste (TiH2 paste in this example) is then baked at 80-150°C to remove the organic phase in the active composite solder paste and achieve a good combination of the TiH2 powder and the AgCu foil, thereby producing an AgCuTi active composite solder.

[0025] Preparation process of Example 1 Reactive coating printing process such as Figure 1 As shown, first, AgCu 28 The metal foil 1 is placed under the 250 mesh screen 2. 28 The AgCu foil and the screen 2 are tightly attached, and the TiH2 active composite solder paste 3 is spread on one side of the screen 2. The scraper 4 is used to apply a force of 0.6 MPa to print the TiH2 active composite solder paste 3 to the other side. The printing speed is 20 mm / s and the scraper angle is 65°. 28 The surface of the foil 1 is printed with a Ti-containing active composite solder paste coating 5. The active composite solder paste coating 5 can present a gradient composite structure, with the surface layer being a porous active compound layer and the interface region being an interdiffusion region between the AgCu alloy and the active element. The AgCuTi active composite solder obtained after the active composite solder paste coating 5 is baked is as follows: Figure 2 shown.

[0026] Example 2: The active composite solder paste was prepared by mixing ZrH2 powder with a particle size of 5 μm and ethyl cellulose solution in a mass ratio of 3:1. The active composite solder paste was prepared by using a 200 mesh screen, a 0.4 MPa scraper pressure, a 70° scraper angle, and a 30 mm / s scraper speed on the AgCu 28 An active layer is printed on the foil surface and dried at 120°C to produce a Zr-containing active brazing filler metal. When brazing Si3N4 ceramic and oxygen-free copper, the active element Zr preferentially reacts with SiO2 on the Si3N4 surface to form a Zr-O-Si transition layer. The resulting joint shear strength reaches 215 MPa, an 18% improvement over conventional AgCuTi brazing filler metal.

[0027] The present application can also form a multi-layer (three or more layers) active composite solder by screen printing active composite solder pastes made of different raw materials multiple times. Figure 3 The active composite solder can be screen-printed twice, wherein the first screen printing uses TiH2 active metal and the second screen printing uses ZrH2 active metal, thereby forming a three-layer structure active composite solder with a ZrH2 active metal layer on the surface, a TiH2 active metal layer in the middle, and a metal foil below.

Claims

1. An active composite brazing filler metal suitable for welding ceramics and copper materials, characterized by: It consists of a plastic base layer and an active coating; the plastic base layer is a metal foil containing at least one element of Ag, Cu, and Ni; the active coating is an active metal layer arranged on the plastic base layer, and the active metal is selected from at least one of Ti, Zr, Cr, Hf, V, and Nb.

2. The active composite brazing filler metal suitable for welding ceramics and copper materials according to claim 1, characterized in that: The active coating layer consists of two layers, with an upper ZrH2 active metal layer and a lower TiH2 active metal layer.

3. The active composite brazing filler metal suitable for welding ceramics and copper materials according to claim 1, characterized in that: The thickness of the metal foil is between 0.01 mm and 0.3 mm, and the maximum length and width are both between 20 mm and 200 mm.

4. The active composite brazing filler metal suitable for welding ceramics and copper materials according to claim 1, characterized in that: The active coating is formed by mixing active metal powder with a particle size of 0.5 micron to 80 micron and an organic carrier.

5. The active composite brazing filler metal suitable for welding ceramics and copper materials according to claim 1, characterized in that: The mass ratio of the plastic matrix layer to the active coating is between 99.5:0.5 and 70:30, and the thickness of the active coating is between 10 microns and 200 microns.

6. The active composite brazing filler metal suitable for welding ceramics and copper materials according to claim 1, characterized in that: The metal foil is AgCu 28 The active coating is TiH2 active solder.

7. The method for preparing the active composite solder suitable for welding ceramics and copper materials according to any one of claims 1 to 6, characterized in that The following steps are involved: S1 prepares metal foil and active composite solder paste; The S2 active composite solder paste is placed on the metal foil through a coating process; S3 The metal foil coated with active composite solder paste is baked at 80~150℃ to form active composite solder.

8. The method for preparing the active composite solder suitable for welding ceramics and copper materials according to claim 7, characterized in that: The active composite solder paste is prepared by mixing the active metal powder according to claim 1 with an organic carrier.

9. The method for preparing the active composite solder suitable for welding ceramics and copper materials according to claim 7, characterized in that: The active composite solder paste is provided on the metal foil through a coating process, comprising: S21 Place the metal foil under the screen and fit it tightly; The S22 active composite solder paste is spread on one side of the screen, and the active composite solder paste is printed on the other side using a scraper.

10. The method for preparing the active composite solder suitable for welding ceramics and copper materials according to claim 7, characterized in that: The active composite solder paste is provided on the metal foil through a coating process, comprising: S23 is to screen print a certain active composite solder paste on the metal foil; S24 another active composite solder paste is screen printed on the metal foil 2.